(untitled) (Experimental biology, 2015)
Actinomycetes constitute the prevalent or at least significant component of the microbiocenosis in the researched soil types of Ili-Balkhash region: light siernozems, common siernozems , alluvial meadow gray soils, and meadow soils. Content of actinomycetes in the total bacterial mass decreases in the samples of meadow swamp soils and swamp soils. In all soil types, there was noted the concentration of actinomycetes in the plant rhizosphere, where their number and their content in the total bacterial biomass considerably increases.